Multicriteria Selection of Friction Stir Welded Al-Tib2 Metal Matrix Composites using WASPAS to Improve Composite Development and Design - Onoyeyan Onajite; Sunday Ayoola Oke (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2020)
The unique area of friction stir welding that involves Al-TiB2 composite development stirs controversy and fails to offer a clear understanding of how to choose the best composite among alternatives without subjectivity. At present, the experienced fabricator uses intuition in judgement, leading to wrong or inconsistent decisions. In this paper, the WASPAS multicriteria model is deployed to choose the best Al-TiB2 composite among options using tensile strength, ductility and microhardness as attributes. The procedure generally entails normalization, preference score and ranking determination and literature data was used. The emerging conclusion from this study is that irrespective of the weight determination method and the multicriteria model adopted to evaluate the alternative fabricated Al-TiB2 composites, the Al-10%TiB2 and Al6065 based alloy always reveal as the best and worst composites, respectively, even under varied normalisation methods. The research confirmed that multicriteria analysis is a potential objective method to choose among fabricated alternatives. The work showed that there is scope to evade the consequences of subjectivity in composite decision making by attaching adequate weights to the deciding factors thereby avoiding misguidance and incorrect decision making. Furthermore, multicriteria models offer novel approaches to understand the relative preference of fabricating composites to one another in the metal matrix composite development area.